2017
DOI: 10.3233/ch-168022
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the evidence: Exploring the effects of exercise on diabetic microcirculation

Abstract: Diabetes mellitus (DM) is associated with cardiovascular complications. Impairment of glycemic control induces noxious glycations, an increase in oxydative stress and dearangement of various metabolic pathways. DM leads to dysfunction of micro- and macrovessels, connected to metabolic, endothelial and autonomic nervous system. Thus, assessing vascular reactivity might be one of the clinical tools to evaluate the impact of harmful effects of DM and potential benefit of treatment; skin and skeletal muscle microc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 117 publications
0
10
0
Order By: Relevance
“…In addition to suggesting a positive influence of exercise training on endothelial function in patients with type 2 diabetes, our study showed that the improvement in endothelial function in response to chronic exercise training was weakened in patients with type 2 diabetes compared with those without. Although the exact mechanism is not well understood, it is speculated that the presence of diabetes may compromise the ability of the endothelium to endogenously increase vascular nitric oxide bioavailability following exercise training [ 31 ], possibly because of the persistent hyperglycemia and the increased levels of circulating advanced glycation end products or reactive oxygen species [ 46 , 47 ]. Moreover, the blunted potential of exercise to stimulate and to mobilize endothelial progenitor cells observed in diabetic patients compared with non-diabetic controls might also contribute to the weakened improvement in endothelial function in response to exercise among type 2 diabetes [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to suggesting a positive influence of exercise training on endothelial function in patients with type 2 diabetes, our study showed that the improvement in endothelial function in response to chronic exercise training was weakened in patients with type 2 diabetes compared with those without. Although the exact mechanism is not well understood, it is speculated that the presence of diabetes may compromise the ability of the endothelium to endogenously increase vascular nitric oxide bioavailability following exercise training [ 31 ], possibly because of the persistent hyperglycemia and the increased levels of circulating advanced glycation end products or reactive oxygen species [ 46 , 47 ]. Moreover, the blunted potential of exercise to stimulate and to mobilize endothelial progenitor cells observed in diabetic patients compared with non-diabetic controls might also contribute to the weakened improvement in endothelial function in response to exercise among type 2 diabetes [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanism is not well understood, it is speculated that the presence of diabetes may compromise the ability of the endothelium to endogenously increase vascular nitric oxide bioavailability following exercise training [ 31 ], possibly because of the persistent hyperglycemia and the increased levels of circulating advanced glycation end products or reactive oxygen species [ 46 , 47 ]. Moreover, the blunted potential of exercise to stimulate and to mobilize endothelial progenitor cells observed in diabetic patients compared with non-diabetic controls might also contribute to the weakened improvement in endothelial function in response to exercise among type 2 diabetes [ 46 ]. These may indicate that more interventions apart from promoting physical exercise might be needed for patients with type 2 diabetes to obtain comparable health benefits like healthy or non-diabetic controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 , 5 This condition is usually a direct result of a combination of genetic predisposition, physical inactivity, and poor eating habits. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…There is strong evidence in the literature 6 , 10 showing that physical activity helps in glycemic control by improving tissue sensitivity to insulin and reducing body weight. Increased blood glucose uptake by muscles may also result from enhanced action of the insulin-regulated GLUT4.…”
Section: Introductionmentioning
confidence: 99%